Epistemische Interpretation glottodidaktischer Theorien der Nachkriegszeit - SKOWRONEK, Barbara (Wydawnictwo Naukowe UAM, 1997)
The goal of this article is to approach a justification by glottodidactic facts of social theories of language communication competence (Zgółka 1980) as well as the social theory of language aquisition competence (Wł. Zabrocki 1980).